FITV 1111: Anime Goes to College Syllabus - Emilie Waggoner (Journal of Anime and Manga Studies)
As universities and colleges face the impending "enrollment cliff" of 2025, many institutions are implementing high-impact practices (HIPs), such as first-year seminars, learning communities, intrusive advising, and co-curricular experiences to attract students. One key feature of first-year seminars tends to be the special topic focus of the courses, which tend to mix current pop culture or sociocultural events into subject matter areas such as psychology, philosophy, music, and science. This paper provides an example syllabus and course set-up for a popular first-year seminar course at the University of Colorado Denver called FITV 1111: Anime Goes to College. By incorporating anime as the main subject matter, students in the course apply student development theory to various anime shows and movies to analyze the characters and understand how their own development in college is impacted by their environment and the media they consume. At the end of the course, students walk away with an understanding of how fictional worlds and fandom spaces can be places for fans to explore their own identities through the characters in the shows.